Pengaruh Sistem Informasi terhadap Kualitas Laporan Keuangan pada Kantor KPP Pratama Bireuen - Handry Eldo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of implementing information systems on the quality of financial reports at the KPP Pratama Bireuen office. This research uses quantitative descriptive methods, with primary and secondary data sources. Data collection techniques use questionnaire and documentation methods. The results of this research show that the implementation of information systems has a significant effect of 70,2% on the quality of financial reports.